What people study when they study Tumblr - Attu, Rose; Terras, Melissa (Journal of documentation, 2017)
Purpose Since its launch in 2007, research has been carried out on the popular social networking website Tumblr. The purpose of this paper is to identify published Tumblr-based research, classify it to understand approaches and methods, and provide methodological recommendations for others. Design/methodology/approach Research regarding Tumblr was identified. Following a review of the literature, a classification scheme was adapted and applied, to understand research focus. Papers were quantitatively classified using open coded content analysis of method, subject, approach, and topic. Findings The majority of published work relating to Tumblr concentrates on conceptual issues, followed by aspects of the messages sent. This has evolved over time. Perceived benefits are the platform’s long-form text posts, ability to track tags, and the multimodal nature of the platform. Severe research limitations are caused by the lack of demographic, geo-spatial, and temporal metadata attached to individual posts, the limited Advanced Programming Interface, restricted access to data, and the large amounts of ephemeral posts on the site. Research limitations/implications This study focusses on Tumblr: the applicability of the approach to other media is not considered. The authors focus on published research and conference papers: there will be book content which was not found using the method. Tumblr as a platform has falling user numbers which may be of concern to researchers. Practical implications The authors identify practical barriers to research on the Tumblr platform including lack of metadata and access to big data, explaining why Tumblr is not as popular as Twitter in academic studies. Social implications This paper highlights the breadth of topics covered by social media researchers, which allows us to understand popular online platforms. Originality/value There has not yet been an overarching study to look at the methods and purpose of those who study Tumblr. The authors identify Tumblr-related research papers from the first appearing in 2011 July until 2015 July. The classification derived here provides a framework that can be used to analyse social media research, and in which to position Tumblr-related work, with recommendations on benefits and limitations of the platform for researchers.